2013
DOI: 10.1016/j.jsat.2013.04.004
|View full text |Cite
|
Sign up to set email alerts
|

A latent class approach to treatment readiness corresponds to a transtheoretical (“Stages of Change”) model

Abstract: Motivation for treatment among people with substance use problems is an important aspect of treatment success. Models for treatment motivation are widely debated. Latent Class Analysis can help to demonstrate the appropriateness of available models. The current study utilizes Latent Class Analysis to analyze treatment readiness statements as they relate to the reduction or cessation of marijuana, cocaine, and opioid use among 539 cocaine and opioid users recruited from the community of Baltimore, MD, USA. Part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 74 publications
0
11
0
Order By: Relevance
“…It is known that expectancies can be altered by instructions or media campaigns 54,67 and are associated with different aspects of desire to change substance use behaviors. 68 As regulations for e-cigarettes are debated, this information can help guide labeling requirements, advertising restrictions, and the development of counter-messaging to discourage unhealthy behaviors. Expectancies may be targets for public health efforts to discourage de novo e-cigarette use among youth and adults, to encourage switching from cigarettes to e-cigarettes, or to encourage e-cigarette use after (or potentially even before) trying NRT and other approved medications, depending on the outcomes of future safety and efficacy studies.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that expectancies can be altered by instructions or media campaigns 54,67 and are associated with different aspects of desire to change substance use behaviors. 68 As regulations for e-cigarettes are debated, this information can help guide labeling requirements, advertising restrictions, and the development of counter-messaging to discourage unhealthy behaviors. Expectancies may be targets for public health efforts to discourage de novo e-cigarette use among youth and adults, to encourage switching from cigarettes to e-cigarettes, or to encourage e-cigarette use after (or potentially even before) trying NRT and other approved medications, depending on the outcomes of future safety and efficacy studies.…”
Section: Discussionmentioning
confidence: 99%
“…[43] The results reported that TTM was used more in healthcare context than treatment and prevention of CDs. In healthcare context, TTM was used to change exercise behaviors,[8444546474849] change the attitude of diet behaviors,[5051525354] addiction treatment behaviors,[55565758] air pollution prevention behaviors,[43] and oral health behaviors. [59]…”
Section: Resultsmentioning
confidence: 99%
“…For instance, there is some overlap between a “treatment readiness statement” and the language in the item, as the item uses the words “ I will ”, which explicitly taps into commitment language. 11 This may have caused some individuals to respond as ‘Unsure’, as opposed to using wording without commitment language for the item (e.g., “What do you expect will be the outcome of your treatment?”). We also found that those with a higher motivation score were more likely to be in the ‘Sure’ group, indicating that while the constructs of outcome expectations and motivation are distinct, they may be related.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to outcome expectations, motivation has been associated with substance use treatment outcomes and treatment retention. 11 While motivation for treatment and treatment expectations are related, there is some evidence that these two constructs may be discriminable. 8 For instance, an individual may be motivated to change substance use behaviors, but at the same time expect that treatment will not be effective in doing so.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation